EFFECTIVENESS OF PUBLIC ENVIRONMENTAL POLICIES IN REDUCING CARBON EMISSION IN NIGERIA - Udoffia, David Thompson; Effanga, Anthony Bassey (African Journal of Social and Behavioural Sciences, 2025)
This work evaluated the Effectiveness of Public Environmental Policies in Reducing Carbon Emissions in Nigeria. The scope of the study spanned from 1990 to 2022. An ex-post facto research design was adopted. The objectives were to examine the impact of public environmental policies on carbon emissions in Nigeria and the relationship between public environmental policies and carbon emissions in Nigeria. To achieve the stated objectives of this work, ARDL Bounds Test technique was used. From the findings, the study discovered a positive and significant impact of public environmental policies on carbon emissions in Nigeria. A long-run relationship was found between public environmental policies and carbon emissions in Nigeria, as validated by the ARDL Bounds test. The Error Correction Model revealed evidence of a strong speed of adjustment in case of short-run distortions in carbon emission towards meeting the long-run equilibrium. Since the positive and significant impact of public environmental policies on reducing carbon emission was found both in the short-run and long-run, there is the need to strengthen the implementation of public environmental policies by enforcing the implementation of the policies by the government to ensure their maximum impact. Also, there is a need to ensure the adequate transition to renewable energy sources and support policies that can transition to cleaner energy options with a significant reduction of carbon emissions in Nigeria. Finally, policymakers should prioritise and incentivise sustainable farming practices that decrease emissions while maintaining productivity.